Thinking about property from antiquity to the age of revolution - Garnsey, Peter 1938- (Cambridge Univ. Press, 2007)
This work explores the historical development of some central themes about property through the ages.
Keywords: Geschichte 700 v. Chr.-1830; Ethik; Geschichte; Philosophie; Religion; Personal property; Personal property -- Moral and ethical aspects; Property -- Philosophy -- History; Property -- Religious aspects; Right of property -- History; Eigentum